Pemberlakuan Arbitrase Secara Elektronik Sebagai Penyelesaian Sengketa Bisnis pada Masa Pandemi COVID-19 - Oedoyo, Wibisono; Herangga, Herangga; Putri Hermin Purnomo, Priscillia; Arvin Wicaksono, Muhammad (CV. Publikasi Indonesia, 2022)
Adjustment of relations between parties and places of communication is not only pegged to space and time, this happens because of the sophisticated technology and ease of communication that has developed rapidly as a result of the big changes in the Industrial Revolution Era 4.0. The activity of resolving business dispute problems during this pandemic is greatly helped by the existence of electronic arbitration whose implementation process can be carried out using various existing arbitration institutions. Writing this journal aims to explain and urge the public that resolving business disputes can use arbitration institutions and be accompanied by legal force. Using normative and empirical legal research methods is the right solution in compiling this research, and taking a legislative and comparative law approach is expected to complete this research. As long as the provisions of Law no. 30 of 1999 concerning Arbitration and Alternative Dispute Resolution (UUAAPS) goes hand in hand, so the electronic arbitration arrangements and procedures remain in effect. The need for Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions as the legal basis for supporting the provisions of Article 4 paragraph (3) of the AAPS Law is to strengthen the regulations in Article 4 paragraph (3) of the AAPS Law. So it can be concluded that carrying out Electronic Arbitration in Indonesia during the COVID-19 pandemic is very helpful for business actors to be able to resolve their disputes because the convenience of these electronic devices makes business actors more efficient in running their companies.